2017
DOI: 10.1080/14767058.2017.1358264
|View full text |Cite
|
Sign up to set email alerts
|

Strong impact of ethnicity on effectiveness of the first trimester maternal serum screen of fetal Down syndrome

Abstract: Of 24,885 women including 36 fetuses with Down syndrome, the detection rates were significantly higher with TRR when compared with CRR-RC, 77.8 and 63.9%, respectively, p < .001. Additionally, the false-positive rates were significantly lower with TRR when compared to CRR-RC (7.5 versus 12.5%, respectively, p < .001) Conclusions: The effectiveness of MSS was much better by using our own reference ranges rather than the method of racial factor correction. The important insight is that ethnicity strongly impacts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Actually, several reports on the effectiveness of quad test in developing countries have been published, but most involved a small sample size, including a small number of fetuses with DS (6, 7). Additionally, as already known, ethnicity has a great impact on serum biomarker levels and accuracy of tests, and it cannot completely be corrected by ethnic factors, either in the first trimester or second trimester (8)(9)(10)(11). Accordingly, our research team took advantage of this routine practice to evaluate the effectiveness of the strategy under the service settings of a large-scale unselected population and, also, to compare the diagnostic performance of Quad test based on Western reference models (WM) with ethnic correction and that based on Thai-specific reference models (TM).…”
Section: Introductionmentioning
confidence: 99%
“…Actually, several reports on the effectiveness of quad test in developing countries have been published, but most involved a small sample size, including a small number of fetuses with DS (6, 7). Additionally, as already known, ethnicity has a great impact on serum biomarker levels and accuracy of tests, and it cannot completely be corrected by ethnic factors, either in the first trimester or second trimester (8)(9)(10)(11). Accordingly, our research team took advantage of this routine practice to evaluate the effectiveness of the strategy under the service settings of a large-scale unselected population and, also, to compare the diagnostic performance of Quad test based on Western reference models (WM) with ethnic correction and that based on Thai-specific reference models (TM).…”
Section: Introductionmentioning
confidence: 99%
“…In actual practice, the serum screening applied in the Asian population is based on Caucasian normative models with weight correction and ethnic factor correction, which is different for each biomarker. However, even with the use of ethnic factor correction, the conventional method (Caucasian normative model with ethnic correction) is not as effective as the methods using the models developed from the specific population under consideration [ 7 ]. Accordingly, to be more effective in screening, the normative references of median concentrations of the serum biomarkers in normal pregnancy specific to the population under consideration must be firstly developed.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies demonstrated an association between individual marker levels and rate of SGA, but most of them had only a limited number of women, and it is difficult to implement these findings in actual practice. Moreover, it is well established that racial factors strongly impact on serum marker levels [9][10][11][12][13], and the normative data of serum biomarkers derived from Caucasian women cannot accurately be interpreted when used in other parts of the world. Though several studies have linked abnormal serum marker levels to higher rate of SGA, no study provides objective methods or models derived from individual serum markers that can be clinically used to determine the probability of SGA.…”
Section: Introductionmentioning
confidence: 99%